2020
DOI: 10.1590/0037-8682-0476-2019
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of blood donor test-seeking behavior among health sciences undergraduate students

Abstract: Introduction: This study investigated the prevalence of blood donors' test-seeking behavior and related factors among health sciences undergraduate students. Methods: A total of 750 students were invited. Data regarding sociodemographic and behavioral characteristics, blood donation practices, and test-seeking behavior were collected. Results: Of the invited students, 341 (45.5%) agreed to participate and answered questions regarding test-seeking behavior. The sample comprised 83.1% females, 96.8% singles, 87.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
1
0
2
Order By: Relevance
“…A high prevalence of blood donor test-seeking behavior (14.4) was observed by Miriane et al in their study done on health science undergraduate students. 14 Higher notification rate in first time donors was also observed by Kumari et al in her study. 5 Test seeking behaviour also explains higher response rate in unmarried donors in my study as it is a hassle-free way to get tested for TTI's.…”
Section: Discussionsupporting
confidence: 71%
“…A high prevalence of blood donor test-seeking behavior (14.4) was observed by Miriane et al in their study done on health science undergraduate students. 14 Higher notification rate in first time donors was also observed by Kumari et al in her study. 5 Test seeking behaviour also explains higher response rate in unmarried donors in my study as it is a hassle-free way to get tested for TTI's.…”
Section: Discussionsupporting
confidence: 71%
“… 22 Whereas, another study by Gebresilase H. W. et al reports religion to be one of the significant predictors of knowledge regarding blood donation among students. 23 Similarly, 6% and 7.6% of non-donors indicated religion and cultural belief as to the barrier for not donating blood before, as reported by Javaeed A. et al 14 , and Ugwu N. I. et al 7 respectively. Our study population consists of the Hindu population mostly, and there were no reported restrictions imposed by the Hindu community over blood donation practice.…”
Section: Discussionmentioning
confidence: 77%
“…Os doadores de sangue tendem a apresentar altos níveis de consciência social e coletiva, mas a frequência da doação pode sofrer influência da conveniência e benefício pessoal 12,14 e sociocultural 11,13 . Ideias de doar como ato de altruísmo 17,19,20,23,24 ou devido percepção de responsabilidade cívica, foram fatores motivadores mais constatados, mesmo em meio à pandemia, em países desenvolvidos como Hong Kong 29 e Alemanha 30 ; por outro lado, em países subdesenvolvidos o maior incentivo para doação é o ato de doar para familiares 32 .…”
Section: Discussionunclassified
“…Entender as motivações que norteiam diferentes grupos [10][11][12][13][14] a se tornarem doadores ou não, pode se constituir em uma ferramenta útil na criação de campanhas de doação de sangue. Baseado nisso, e na situação da pandemia de Covid-19 9,15 , que inclusive pode se repetir em outros cenários similares no futuro, buscou-se elaborar um trabalho para identificar conhecimentos, atitudes e práticas (CAP) da doação de sangue dos estudantes de medicina durante a pandemia.…”
Section: Introductionunclassified